2019
DOI: 10.1111/rec.13059
|View full text |Cite
|
Sign up to set email alerts
|

Plant recovery techniques do not ensure biological soil‐crust recovery after gypsum quarrying: a call for active restoration

Abstract: Biological soil crusts (biocrusts) are a key component of dryland ecosystems worldwide. However, large extensions of biocrusts are disturbed by human activities, gypsum quarry being an outstanding example. Restoration techniques applied have offered satisfactory results for vascular plants but they could greatly differ in promoting biocrust recovery. A basic question remains unaddressed: can measures for plant recovery accelerate or promote the recovery of biological crusts? We have examined eight different si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…The lichen crust, still to be recovered, shows and average net growth of around 0.7% per year in Lepraria and 1.7% per year in Squamarina and Diploschistes. Differences between types of crust agree with what was obtained in other works ( Belnap and Warren, 2002 ; Dojani et al, 2011 ; Gypser et al, 2015 ; Williams et al, 2018 , Lorite et al, 2020 , among others). The recovery of the microbial crust ensures a certain stabilization of the soil, which favors the establishment of lichens ( Belnap and Büdel, 2016 ; Deng et al, 2020 ), reduces erosion ( Chamizo et al, 2012a ) and reduces the risk of degradation of these areas ( Belnap, 1995 ; Cantón et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The lichen crust, still to be recovered, shows and average net growth of around 0.7% per year in Lepraria and 1.7% per year in Squamarina and Diploschistes. Differences between types of crust agree with what was obtained in other works ( Belnap and Warren, 2002 ; Dojani et al, 2011 ; Gypser et al, 2015 ; Williams et al, 2018 , Lorite et al, 2020 , among others). The recovery of the microbial crust ensures a certain stabilization of the soil, which favors the establishment of lichens ( Belnap and Büdel, 2016 ; Deng et al, 2020 ), reduces erosion ( Chamizo et al, 2012a ) and reduces the risk of degradation of these areas ( Belnap, 1995 ; Cantón et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Several authors have found that the ability to colonize and the growth rate of microbial crust are greater than that of lichen or moss crust ( Belnap and Eldridge, 2001 ; Dojani et al, 2011 ; Lorite et al, 2020 ; among others). In fact, this could be perhaps the only certainty to date in relation to succession in biocrusts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interest in assisted biocrust establishment using single or multiple biocrust species has recently increased, often to restore ecological benefits (Pointing & Belnap 2012; Bu et al 2013; Zhao et al 2016; Antoninka et al 2018). No known research addresses propagation and dispersal of lichen biocrusts for restoration in arctic tundra, although studies assessed assisted dispersal of biocrusts in alpine environments (Letendre et al 2019), and lichens in other ecosystems (reviewed in Smith 2014) including reindeer husbandry (Roturier et al 2007; Roturier & Bergsten 2009), endangered species conservation (Lidén et al 2004), lichen biodiversity maintenance in managed forests (Sillett & McCune 1998; Hazell & Gustafsson 1999; Hilmo 2002), and restoration (Duncan 2011; Gypser et al 2015; Ballesteros et al 2017; Lorite et al 2020). Inoculation techniques commonly assessed in the growth chamber and field have included transplantation of whole crust pieces, sieving crust material to simulate natural vegetative fragmentation, dry or wet (in a slurry) dispersal, and spreading of individual species (Belnap 1993; Scarlett 1994; Roturier & Bergsten 2009; Stewart & Siciliano 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some other studies have also evaluated the linkages and interactions between all these positive effects of biocrusts and the performance of other living natural resources (5 %) such as vascular plants (i.e. Luzuriaga et al, 2012;Rodriguez-Caballero et al, 2018b) or vertebrates (Eldridge et al, 2010;Fig. 2).…”
Section: Resultsmentioning
confidence: 99%